Maternal Outcomes of Unengaged Fetal Head in Primigravida in DHQ Hospital, Dera Ismail Khan, Pakistan - Irum Batool Hashmi, Najma Bibi, Mehak Jacob, Neelam Mehsood, Shazia Bibi, Rida Asghar (Pakistan Journal of Medical & Health Sciences, 2024)
Introduction: The fetal head station denotes the specific position of the fetal head within the maternal birth canal, as assessed through digital vaginal examination. Primigravida individuals constitute a demographic characterized by elevated risk, wherein an elevated fetal head position in this group is considered a significant risk factor for labor dystocia. There is very limited data in this subject in our local population, therefore it’s a dire need to get local evidence. Objective: This study aims to evaluate the maternal outcomes associated with an unengaged fetal head in primigravida patients presenting at DHQ Hospital Dera Ismail Khan. Study Design: Descriptive Case Series. Setting: Obstetrics and Gynecology Department, DHQ Hospital Dera Ismail Khan. Duration of Study: The period of this investigation spanned from the 10th of September 2022 to the 10th of March 2023. Subjects and Methods: A cohort comprising 157 primigravida women exhibiting an unengaged fetal head was incorporated into the study. All participants underwent delivery in accordance with the established departmental protocols and were monitored until the 15th day postpartum. Maternal outcomes (vaginal delivery, forceps delivery, cesarean section, postpartum hemorrhage and wound infection) were noted. Results: The age spectrum investigated in this research was between 18 and 35 years, exhibiting an average age of 27.127 ±3.29years, while the average gestational age was recorded as 6.615±1.82 weeks. Vaginal Delivery was observed in 58.6% patients, Forceps Delivery 16.6%, C-Section 24.8%, Postpartum Hemorrhage 26.8% and Wound Infection was 15.3 %. Conclusion: Our study has determined that the presence of an unengaged fetal head in primigravida women experiencing spontaneous onset of labor does not constitute a contraindication for the performance of a lower segment cesarean section (LSCS). Keywords: Unengaged fetal head, Primigravida, Maternal outcomes